Two Birds with One Stone: Possible Dual-Role of Oxytocin in the Treatment of Diabetes and Osteoporosis - Elabd, Seham; Sabry, Ismail (Frontiers in Endocrinology, 2015)
Oxytocin, a hormone most commonly associated with labor and lactation, may have a wide variety of physiological and pathological functions, which makes oxytocin and its receptor potential targets for drug therapy. In this review, we highlight the newly discovered metabolic role of oxytocin in diabetes and its complication; such as diabetic osteopathy. Oxytocin may have positive metabolic effects; this is based on the change in glucose metabolism, lipid profile, and insulin sensitivity. It may modify glucose uptake and insulin sensitivity both through direct and/or indirect effects. It may also cause regenerative changes in diabetic pancreatic islet cells. Moreover, it has an anabolic effect on the bone biology. So, the activation of the oxytocin receptor pathway by infusion of OT, OT analogs, or OT agonists may represent a promising approach for the treatment of diabetes and some of its complications, including diabetic osteopathy.